Thyroid Hormone Decreases Hepatic Steatosis, Inflammation, and Fibrosis in a Dietary Mouse Model of Nonalcoholic Steatohepatitis - Zhou, Jin; Tripathi, Madhulika; Ho, Jia Pei; Widjaja, Anissa Anindya; Shekeran, Shamini Guna; Camat, Macalinao Dominique; James, Anne; Wu, Yajun; Ching, Jianhong; Kovalik, Jean-Paul; Lim, Kiat-Hon; Cook, Stuart Alexander; et al. (Thyroid (New York, N.Y.), 2022)
Nonalcoholic steatohepatitis (NASH) is characterized by hepatic steatosis, lobular inflammation, and fibrosis. Thyroid hormone (TH) reduces steatosis; however, the therapeutic effect of TH on NASH-associated inflammation and fibrosis is not known. This study examined the therapeutic effect of TH on hepatic inflammation and fibrosis during NASH and investigated THs molecular actions on autophagy and mitochondrial biogenesis. HepG2-TRβ cells were treated with bovine serum albumin-conjugated palmitic acid (PA) to mimic lipotoxic conditions . Mice with NASH were established by feeding C57BL/6J mice Western diet with 15% fructose in drinking water for 16 weeks. These mice were administered triiodothyronine (T3)/thyroxine (T4) supplemented in drinking water for the next eight weeks. In cultured HepG2-TRβ cells, TH treatment increased mitochondrial respiration and fatty acid oxidation under basal and PA-treated conditions, as well as decreased lipopolysaccharides and PA-stimulated inflammatory and fibrotic responses. In a dietary mouse model of NASH, TH administration decreased hepatic triglyceride content (3.19 ± 0.68 vs. 8.04 ± 0.42 mM/g liver) and hydroxyproline (1.44 ± 0.07 vs. 2.58 ± 0.30 mg/g liver) when compared with mice with untreated NASH. Metabolomics profiling of lipid metabolites showed that mice with NASH had increased triacylglycerol, diacylglycerol, monoacylglycerol, and hepatic cholesterol esters species, and these lipid species were decreased by TH treatment. Mice with NASH also showed decreased autophagic degradation as evidenced by decreased transcription Factor EB and lysosomal protease expression, and accumulation of LC3B-II and p62. TH treatment restored the level of lysosomal proteins and resolved the accumulation of LC3B-II and p62. Impaired mitochondrial biogenesis was also restored by TH. The simultaneous restoration of autophagy and mitochondrial biogenesis by TH increased β-oxidation of fatty acids. Additionally, the elevated oxidative stress and inflammasome activation in NASH liver were also decreased by TH. In a mouse model of NASH, TH restored autophagy and mitochondrial biogenesis to increase β-oxidation of fatty acids and to reduce lipotoxicity, oxidative stress, hepatic inflammation, and fibrosis. Activating thyroid hormone receptor in the liver may represent an effective strategy for NASH treatment.